Board of directors, shariah committees and sustainability commitment of Islamic banks in Malaysia / Siti Nurain Muhmad ...[et al.] - Muhmad, Siti Nurain; M. Ariff, Akmalia; Abd Majid, Norakma; Zainul Abidin, Ahmad Firdhauz (UiTM Press, 2021)
This study examined the relationship between board of directors, Shariah committee and sustainability commitment of Islamic banks in Malaysia. Analyses were performed on a sample of 16 Islamic banks in Malaysia from 2017 to 2018, consisting of 11 local and 5 foreign banks. Regression analyses involved characteristics of the board of directors and Shariah committees as the independent variables and sustainability commitment as the dependent variable. Three corporate characteristics (board size, women on the board and Shariah committee) proxy for strategic leadership, while sustainability commitment was based on the framework of the Sustainable Development Goals consisting of economic, social, and environmental dimensions. The results showed that board size was not associated, while women on the board was negatively associated, with the banks' sustainability commitment. Additionally, the Islamic banks with a larger number of members in the Shariah committee had greater sustainability commitment compared to their counterparts. Thus, this study confirms that Shariah committee as an essential factor in achieving the Islamic banks' sustainability commitment goals. The findings suggest more concerted efforts to embed strategic leadership from the top to achieve appropriate levels of effectiveness that can reflect better responses to sustainability commitment issues.